Stress Testing the USA - Short, John Rennie. author. (orcid)0000-0001-7141-6626 Link aut Link
V, 188 p. 1 illus.
Keywords: Stress tests highlight a system’s weak spots. This second edition provides a stress testing of the United States by exploring in detail the background to the disasters of the War on Terror, Hurricane Katrina, the financial crisis, the Gulf oil spill and the COVID-19 epidemic. These major stresses—the country’s longest war, its biggest natural disaster, its biggest financial collapse since the Great Depression, its biggest oil spill and its worst pandemic since the influenza pandemic of 1918—tell us much about structural flaws in the United States. This book explores each of these events in detail to locate the seed of the disasters, and highlights what we have learned and not learned from these stress tests. John Rennie Short is Professor of Public Policy at the University of Maryland Baltimore County, USA.